Yoga-based exercise to prevent falls in community-dwelling people aged 60 years and over: study protocol for the Successful AGEing (SAGE) yoga randomised controlled trial. Issue 1 (29th September 2020) - Oliveira, Juliana S; Sherrington, Catherine; Lord, Stephen; Sesto, Romina; Youkhana, Sabrina; Camara, Giane C; Grunseit, Anne C; Bauman, Adrian; Anstey, Kaarin J; Shepherd, Roberta B; Tiedemann, Anne
Abstract : Introduction: Falls significantly reduce independence and quality of life in older age. Balance-specific exercise prevents falls in people aged 60+ years. Yoga is growing in popularity and can provide a high challenge to balance; however, the effect of yoga on falls has not been evaluated. This trial aims to establish the effect on falls of a yoga exercise programme compared with a yoga relaxation programme in community-dwellers aged 60+ years. Method and Analysis: This randomised controlled trial will involve 560 community-dwelling people aged 60+ years. Participants will be randomised to either: (1) the Successful AGEing ( SAGE ) yoga exercise programme or (2) a yoga relaxation programme. Primary outcome is rate of falls in the 12 months post randomisation. Secondary outcomes include mental well-being, physical activity, health-related quality of life, balance self-confidence, physical function, pain, goal attainment and sleep quality at 12 months after randomisation. The number of falls per person-year will be analysed using negative binomial regression models to estimate between-group difference in fall rates. Generalised linear models will assess the effect of group allocation on the continuously scored secondary outcomes, adjusting for baseline scores. An economic analysis will compare the cost-effectiveness and cost-utility of the two yoga programmes. Ethics and dissemination: Protocol was approved by the Human Research Ethics Committee at The University of Sydney, Australia (approval 2019/604). Trial results will be disseminated via peer-reviewed articles, conference presentations, lay summaries. Trial registration number: The protocol for this trial is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12619001183178).